2023
DOI: 10.3390/microorganisms11020425
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Drug Resistance Patterns of Mycobacterium tuberculosis in High-Burden Area in Western Siberia, Russia

Abstract: Russia is a high-burden area for multidrug-resistant tuberculosis (MDR-TB). Here, we studied the epidemiological situation and drug resistance patterns of Mycobacterium tuberculosis in the Omsk region in Western Siberia. M. tuberculosis isolates (n = 851) were recovered from newly diagnosed TB patients in 2021. The isolates were tested by bacteriological and molecular methods, and long-term epidemiological data were analyzed. The TB incidence dec, this is not variablereased from 93.9 in 2012 to 48.1 in 2021, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“…However, in the study, there was no RIF-mono resistant isolate found, and all RIF-related resistant cases were also resistant to INH-related which are known as MDR-TB cases, which has significant implications since practicing TB programs to use RIF-resistance as a surrogate marker for MDR-TB diagnosis and is an essential drug during the course of TB treatment. Compared to our findings, previous studies were reported higher rate of INH-mono resistant from Western Kenya (28.5%) 36 and RIF-mono resistant from Amhara region (6%), 34 Western Kenya (14.6%), 36 Tanzania (2.5%), 41 and Zambia (3%); 37 as well as lower rate of any mono-resistant to tested drugs from Russia (13.9%), 42 INH mono-resistant from Amhara region (2%) 34 and Zambia (9.8%), 37 and STR-mono resistant from Zambia (0.8%) 37 among TB patients.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…However, in the study, there was no RIF-mono resistant isolate found, and all RIF-related resistant cases were also resistant to INH-related which are known as MDR-TB cases, which has significant implications since practicing TB programs to use RIF-resistance as a surrogate marker for MDR-TB diagnosis and is an essential drug during the course of TB treatment. Compared to our findings, previous studies were reported higher rate of INH-mono resistant from Western Kenya (28.5%) 36 and RIF-mono resistant from Amhara region (6%), 34 Western Kenya (14.6%), 36 Tanzania (2.5%), 41 and Zambia (3%); 37 as well as lower rate of any mono-resistant to tested drugs from Russia (13.9%), 42 INH mono-resistant from Amhara region (2%) 34 and Zambia (9.8%), 37 and STR-mono resistant from Zambia (0.8%) 37 among TB patients.…”
Section: Discussioncontrasting
confidence: 93%
“…The overall prevalence of MDR-TB among all studied TB patients was 12/168 (7.1%), which is in agreement with the studies conducted from Saudi Arabia (5%), 39 Zambia (9.8%), 37 and Tanzania (5.7%) 41 among TB patients. While, the higher rate of MDR-TB was reported from Russia (67.9%), 42 North India (17.4%), 35 and Amhara region (87%) 34 among the RIF-resistant patients. Our study also revealed that the MDR-TB isolates among HIV-positive vs HIV-negative patients was found to be 5/36 (13.9%) vs 7/132 (5.3%), respectively.…”
Section: Discussionmentioning
confidence: 86%
“…MDR-TB is one of the leading causes of death due to antimicrobial resistance, accounting for one in three antimicrobial resistance-related deaths [ 56 ]. The number of MDR-TB infections is particularly worrying in China, India, and the Russian Federation [ 56 , 57 ].…”
Section: Epidemiology Of Tuberculosismentioning
confidence: 99%
“…According to the best estimates, rifampicin-resistant tuberculosis (RR-TB), the most effective fi rst-line treatment, affected 558 000 persons worldwide in 2017 (range: 483000-639000), and 82% of these individuals had MDR-TB, or multidrug-resistant tuberculosis. Nearly half of all MDR/RR-TB cases worldwide in 2021 were found in three nations: Pakistan (7.9%), China (14%) and the Russian Federation (8.5%), as well as India (26%) (Kostyukova et al 2023).…”
Section: Introductionmentioning
confidence: 99%